OPTIMALISASI PENDIDIKAN KARAKTER DENGAN METODE PEMBIASAAN - Irma Dahlia; R. Gunawan Sudarmanto; Pargito Pargito (Faculty of Teacher Training and Education, University of Lampung, 2013)
This research aimed to describe learning application with customized method that could increase optimize characterized value education. This education was done by using PTK. The research result could be seen from the average score of the class before using customized method whereas the accomplishment were only 15 of 46 students. The increase of average scores of the class arrived to the criteria as 80%. The characterized education by using customized method could the increase of average scores of the class arrived to the criteria expected as 80%. (2) the application of learning by using customized method could cycle 1 until cycle 3, students character like honest, hard work, tolerant, friendly, creative, and communicative, independent, curious and eager to read became increased.Penelitian ini bertujuan mendeskripsikan pelaksanaan pembelajaran dengan metode pembiasaan dapat mengoptimalkan pendidikan nilai karakter. Penelitian ini menggunakan PTK. Hasil penelitian dapat dilihat dari rata-rata nilai kelas sebelum menggunakan metode pembiasaan yang tuntas hanya 15 siswa dari 46 orang. Peningkatan nilai rata-rata kelas telah memenuhi kriteria sebesar 80%. Pelaksanaan pembelajaran dengan metode pembiasaan dari siklus 1 sampai siklus 3, karakter siswa seperti kejujuran, kerja keras, toleransi, bersahabat, kreatif, toleransi dan kominkatif, mandiri, rasa ingin tahu dan gemar membaca selalu mengalami peningkatan.Kata kunci : metode pembiasaan, pendidikan geografi, pendidikan karakter